Laser diagnostics technologies in ophthalmology - Kolarčík, Lukáš; Němčanský, Jan (Lékař a technika, 2008)
Conference paper describes laser scanning technologies widely used for imaging of the retina and the optic disc in ophthalmology. It is particularly focused on the devices used at the Department of Ophthalmology at the Teaching Hospital in Ostrava – GDxVCC (Glaucoma Diagnostics with Variable Corneal Compensation) and OCT (Optical Coherence Tomography). It includes technical principles, clinical applications and experience of usage and operating the devices.
Keywords: optická koherentní tomografie; retina; diagnostické techniky oftalmologické; lidé; Diagnostic Techniques, Ophthalmological; Lasers; macula lutea; Tomography, Optical Coherence; Diabetic Retinopathy; glaukom; diabetická retinopatie; Macula Lutea; Glaucoma; Macular Degeneration; makulární degenerace; Retina; lasery; Humans